A Thematic Analysis of Canine-Assisted Interventions in Educational Settings in Finland - Pliushchik, Marina (My University, 2020)
The aim of the present study was to support further research into canine-assisted interventions (CAIs) by providing small theories about the effectiveness of CAIs in various educational settings. The main research question of this paper was How and Why CAIs produce change in learning, in the opinions of practitioners in the field? This research question was addressed through a number of smaller research questions, linked to the elements of a small theory. In order to answer the research questions, an interview guide was developed based on previous research literature and an instrument applied in previous research. Data was collected through semi-structured interviews with practitioners in the field of CAI across different educational contexts and analyzed with the help of thematic analysis. As a result of the study, three small theories, explaining the effectiveness of CAIs, were developed. According to the small theories, CAIs have a possibility to serve the needs of struggling learners, aiming to improve reading and oral skills and provide them with a more positive learning environment. CAIs influence educational goals indirectly, through improving aspects of the learners’ motivation, self-perception and self-regulation. Moreover, CAIs provide emotional social support and coping assistance. As a result, the clients’ attitude towards learning situations improves, their mood and happiness levels rise, which is seen as a valuable outcome of CAIs across contexts. The practitioners do not directly measure the outcomes of CAIs, but use observation and feedback to evaluate their effectiveness. The small theories can be used in future research as a starting point for new investigations.
Keywords: human-animal interaction, animal-assisted intervention, canine-assisted intervention, thematic analysis, small theory approach, educational settings, animal-assisted education, canine-assisted education, animal-assisted learning